IMPLEMENTASI PROGRAM POJOK BACA DALAM RANGKA MENINGKATKAN LITERASI ANAK USIA DINI DI TK NEGERI 1 ATAP 02 LUBUK PAKAM - Khairani Ulfa; Siti Fadia Annisa; Yasmin Putri Setiawan; Juli Yanti Harahap (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to implement a reading corner program at TK Negeri 1 Atap 02 Lubuk Pakam and analyze its impact on increasing reading interest and literacy skills of early childhood. The results of the study indicate that there are several stages in the implementation of this reading corner program, including socialization to early childhood, making a reading corner, mentoring and implementing the reading corner, and evaluating the implementation of the reading corner